Ultrasonic Nakagami‐parameter characterization of parotid‐gland injury following head‐and‐neck radiotherapy: A feasibility study of late toxicity. Issue 2 (28th January 2014) - Yang, Xiaofeng; Tridandapani, Srini; Beitler, Jonathan J.; Yu, David S.; Wu, Ning; Wang, Yuefeng; Bruner, Deborah W.; Curran, Walter J.; Liu, Tian
Abstract : Purpose: : The study aims to investigate whether Nakagami parameters—estimated from the statistical distribution of the backscattered ultrasound radio‐frequency (RF) signals—could provide a means for quantitative characterization of parotid‐gland injury resulting from head‐and‐neck radiotherapy. Methods: : A preliminary clinical study was conducted with 12 postradiotherapy patients and 12 healthy volunteers. Each participant underwent one ultrasound study in which ultrasound scans were performed in the longitudinal, i.e., vertical orientation on the bilateral parotids. For the 12 patients, the mean radiation dose to the parotid glands was 37.7 ± 9.5 Gy, and the mean follow‐up time was 16.3 ± 4.8 months. All enrolled patients experienced grade 1 or 2 late salivary‐gland toxicity (RTOG/EORTC morbidity scale). The normal parotid glands served as the control group. The Nakagami‐scaling and Nakagami‐shape parameters were computed from the RF data to quantify radiation‐induced parotid‐gland changes. Results: : Significant differences in Nakagami parameters were observed between the normal and postradiotherapy parotid glands. Compared with the control group, the Nakagami‐scaling parameter of the postradiotherapy group decreased by 25.8% ( p < 0.001), and the Nakagami‐shape parameter decreased by 31.3% ( p < 0.001). The area under the receiver operating characteristic curve was 0.85 for the Nakagami‐scaling parameter and was 0.95 for the Nakagami‐shape parameter, which further demonstrated the diagnostic efficiency of the Nakagami parameters. Conclusions: : Nakagami parameters could be used to quantitatively measure parotid‐gland injury following head‐and‐neck radiotherapy. Moreover, the clinical feasibility was demonstrated and this study provides meaningful preliminary data for future clinical investigation.